1992
DOI: 10.1002/ar.1092340310
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of fetal rat lung development

Abstract: The primary aim of this morphological investigation was to elaborate a concept allowing us to coherently define reference spaces for morphometric analysis of fetal lung development. Beyond this quantitative goal, morphological analysis of cell types, definition of compartments, and reflection about the prospective fate of their constituents provided per se new insights into the developmental processes. Lungs of rat fetuses aged 17-23 days and newborns aged 20 hours were fixed with an osmium tetroxide and gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0
2

Year Published

1993
1993
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 24 publications
3
50
0
2
Order By: Relevance
“…These effects included reduced expression of RTI 40 mRNA and its protein as well as diminished surface coverage by type I cells compared with type II cells in the distal potential air spaces. The effects of oligohydramnios on epithelial differentiation, although apparent at 21 days, were more pronounced at 22 days, a time when the prospective air spaces of the fetal rat lung are undergoing dilatation (9).…”
Section: Discussionmentioning
confidence: 92%
“…These effects included reduced expression of RTI 40 mRNA and its protein as well as diminished surface coverage by type I cells compared with type II cells in the distal potential air spaces. The effects of oligohydramnios on epithelial differentiation, although apparent at 21 days, were more pronounced at 22 days, a time when the prospective air spaces of the fetal rat lung are undergoing dilatation (9).…”
Section: Discussionmentioning
confidence: 92%
“…In RFL at Embryonic Day 16, PARP-1 was expressed mainly in peripheral lung parenchyma and in epithelial tubules, regions associated with cell proliferation in pseudoglandular lung (36), as well as dividing cells (Figure 4A), findings consistent with previous observations in vitro of upregulation of PARP-1 in dividing cells (9). In proliferating acute promyelocytic leukemia cells PARP-1 regulates cell cycle progression (6).…”
Section: Discussionsupporting
confidence: 90%
“…This apparent conflict with the data in Figure 1 Immunolocalization showed that PARP-1 expression became progressively more restricted with maturation, so that fewer cells expressed PARP-1, whereas those that continued to express it did so at relatively high levels. The high PARP-1 expression at ed18 corresponds with the onset of terminal differentiation of the gas exchange epithelium (36,37). This finding is consistent with results from the adipocyte (12) and chick limb differentiation models (11), in which predifferentiation peaks in PARP-1 expression and activity were demonstrated.…”
Section: Discussionsupporting
confidence: 88%
“…Looking like a primitive gland, the developing lung enters the pseudoglandular stage. During this period, most of the branching morphogenesis takes place (7). In the subsequent canalicular stage the bronchial tree is established, vascularization increases rapidly, respiratory bronchioli appear, interstitial tissue decreases, and the epithelial barrier thins out as the capillaries begin to lie in close apposition to the epithelium, forming the eventual air-blood barrier (7).…”
Section: Apoptosis and Lung Developmentmentioning
confidence: 99%
“…During this period, most of the branching morphogenesis takes place (7). In the subsequent canalicular stage the bronchial tree is established, vascularization increases rapidly, respiratory bronchioli appear, interstitial tissue decreases, and the epithelial barrier thins out as the capillaries begin to lie in close apposition to the epithelium, forming the eventual air-blood barrier (7). By the end of this stage, airway branching is complete and the distal cuboidal epithelium begins to differentiate into alveolar epithelial type II cells (AEC2) and alveolar epithelial type I cells (AEC1), responsible for surfactant production and gas exchange, respectively (7).…”
Section: Apoptosis and Lung Developmentmentioning
confidence: 99%